Percepções de estudantes de enfermagem sobre o uso da simulação clínica para o ensino e aprendizagem na prevenção, avaliação e tratamento em lesão por pressão - Rocha, Liandra Aparecido Cezario (Universidade Federal de São Carlos, 2022)
Objective: To characterize the knowledge of nursing students before and after expository and dialogued training and the participation, evaluating the implications of clinical simulation on self -confidence and satisfaction of participants after simulated experiences. Method: Methodological study, developed in two steps with use simulated clinical scenarios built through the Fabric Referential and Recommended Practices of the International Nursing Association for Clinical Simulation and Learning. The selection of the judges followed the criteria of Fehring and Snowball Technique, the collection of data occurred in two steps as Delphi. The analysis of the results considered the level of agreement 0.80. Results: Two scenarios were validated resulting in scale-level content Validity Index Global greater than 0.80; Both make up items on the prior knowledge of the apprentice, general objective and specific learning, theoretical foundation, responsible, complexity, documentation, briefing, theme, human and material resources, target audience, Team training, debriefing and evaluation. The analysis of the results in the second stage occurred in two moments, the first with the statistical analysis of the results from the scales and a descriptive analysis of student responses during telessimulation. In the first moment, a descriptive analysis was performed considering the PIEPER Knowledge Test before and after educational intervention. To identify if the average pre and post-intervention points were statistically different, it was considered the signaled classification test of Wilcoxon (1945). After the analysis of the knowledge presented by the participants before and after the intervention, specific evaluations were made about the intervention it self applied, using scales: simulation design scale (EDS) and satisfaction scale of students and self -confidence with learning (ESEAA). Conclusions: Scenarios simulated were validated for the teaching and learning of nursing students, to Evaluate and treat pressure injury in the hospital and home context. The educational strategy of telessimulation used in this study allowed the comparative evaluation of the perceptions of students in prevention, evaluation and treatment in pressure injury, characterizing the level of knowledge in pre and post educational intervention.
Perceptions of nursing students about the use of clinical simulation for teaching and learning in the prevention, evaluation and treatment of pressure injuries
Keywords: Simulação; Lesão por Pressão; Estudantes de Enfermagem; Educação em Enfermagem; Avaliação em Enfermagem; CIENCIAS DA SAUDE::ENFERMAGEM::ENFERMAGEM MEDICO-CIRURGICA